2010
DOI: 10.1242/jcs.068015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the tumor-suppressor protein BRCA2 does not regulate cytokinesis in human cells

Abstract: SummaryGermline mutations in the tumor-suppressor gene BRCA2 predispose to breast and ovarian cancer. BRCA2 plays a well-established role in maintaining genome stability by regulating homologous recombination. BRCA2 has more recently been implicated in cytokinesis, the final step of cell division, but the molecular basis for this remains unknown. We have used time-lapse microscopy, recently developed cytokinesis assays and BAC recombineering (bacterial artificial chromosome recombinogenic engineering) to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Likewise, Jonsdottir et al [55] have demonstrated that BRCA2 mutation carrier fibroblasts had delayed cytokinesis, being the mean cell division time 6 min longer compared with BRCA2 wild-type cells. However, in contrast to results from these two studies, Lekomtsev et al [56] have recently indicated that BRCA2 does not regulate cytokinesis in human cells. Thus, further research is required to verify a role of BRCA2 in the regulation of cell division.…”
Section: Discussionmentioning
confidence: 61%
“…Likewise, Jonsdottir et al [55] have demonstrated that BRCA2 mutation carrier fibroblasts had delayed cytokinesis, being the mean cell division time 6 min longer compared with BRCA2 wild-type cells. However, in contrast to results from these two studies, Lekomtsev et al [56] have recently indicated that BRCA2 does not regulate cytokinesis in human cells. Thus, further research is required to verify a role of BRCA2 in the regulation of cell division.…”
Section: Discussionmentioning
confidence: 61%
“…For this, we took advantage of HeLa cells expressing BAC-encoded fulllength BRCA2, tagged with GFP and FLAG (32). Because HeLa cells carry a short telomere (Ͻ5 kb), telomerase (hTERT) was introduced into these cells to elongate the telomeres and facilitate the telomere-ChIP assay (57).…”
Section: Resultsmentioning
confidence: 99%
“…Telomere-ChIP-HeLa_CFLAP-BRCA2_hTert was generated by introducing hTert by retroviral transfer of pBabe_hTert into HeLa_CFLAP-BRCA2 cells (32). HeLa_CFLAP BRCA2_hTert cells were subjected to double thymidine block.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is tempting to speculate that integrin-regulated, RSK-dependent phosphorylation of filamin A promotes cytokinesis by localizing BRCA2 to the midbody. However, we do not know whether the phosphorylation of filamin A regulates its function at the midbody; furthermore, the role of BRCA2 in cytokinesis is not universally accepted (Lekomtsev et al, 2010).…”
Section: Discussionmentioning
confidence: 99%